Impact of social media advertisement on consumer purchasing behaviour - DR. MAHESH V.J; THANUSHREE H (The journal of contemporary issues in business and government, 2020)
The latest trend in marketing is advertising and purchasing through social media. Currently the majority use social media and are greatly attracted towards the new brands which are advertised in social media. Consumers are highly influenced by online advertisements that come in various social media platforms like Facebook, Instagram, Pinterest, YouTube, etc. social media easily take the attention and impel the consumers to go beyond the window shopping which is purchasing. Social media has become an effective marketing tool to create brand awareness. The consumer’s choices have narrowed down and in need of an influence to convince the consumer choices. Attractive and informative or well drafted content can glue the consumers towards specific brands or services. Surveys have been taken to find specific impacts on the consumers purchasing behaviour through social media advertisements. The main aim of this paper is to study the impact of social media advertising on consumer purchasing behaviour.